Fitting into the collective: a cultural regulatory fit perspective on international student adaptation in China - Li, Jiayu; Zhang, Ting (Frontiers in Psychology, 2025)
Against the backdrop of China's growing international student population, enhancing their subjective wellbeing has become a pressing issue in university management. Drawing on cultural regulatory fit theory, This study investigates the influence mechanism of cultural regulatory fit on the subjective wellbeing of international students in China based on data collected at three time points. The final valid sample size after matching across all three stages is N = 327. A dual mediation model was proposed, incorporating cultural adaptation and identity strain, with individualistic value orientation as a moderator. Results revealed that: (1) cultural regulatory fit promotes adaptation, reduces identity strain, and enhances wellbeing; (2) both mediators play significant roles in this process; and (3) individualistic orientation did not significantly moderate the main pathway, but multi-group analyses confirmed the model's cross-cultural applicability across Asian and non-Asian groups. This study contributes a novel perspective on the dynamic cognitive-emotional mechanisms of adaptation and offers practical insights for psychological support strategies in higher education.